The Sacred Door and Other Stories : Cameroon Folktales of the Beba. - Makuchi, 1958- (Research in international studies. Africa series., 2007)
The Sacred Door and Other Stories: Cameroon Folktales of the Beba offers readers a selection of folktales infused with riddles, proverbs, songs, myths, and legends, using various narrative techniques that capture the vibrancy of Beba oral traditions. Makuchi retells the stories that she heard at home when she was growing up in her native Cameroon. The collection of thirty-four folktales of the Beba showcases a wide variety of stories that capture the richness and complexities of an agrarian society's oral literature and traditions. Revenge, greed, and deception are among t.